Human capital of entrepreneurial teams in nascent high-tech sectors: a comparison between Cleantech and Internet. Issue 1 (2nd January 2018) - Garrone, Paola; Grilli, Luca; Mrkajic, Boris
ABSTRACT: We use an inductive approach to understand what types of founders' human capital, at individual and team levels, are necessary to recognise and exploit entrepreneurial opportunities. A sample of 195 founders who teamed up in the nascent phases of Cleantech and Interned-based sectors is analysed. The results suggest a twofold moderating effect of the sectoral context. First, a more hard science-based and complex sector like Cleantech demands technically more skilled entrepreneurs, but at the same time, it still requires fairly commercially experienced and economically competent individuals. Furthermore, the business context also appears to exert an important influence on team formation dynamics: individuals are more prone to team-up with cofounders possessing complementary know-how when they are starting a new business venture in the Cleantech rather than in the Internet-based sector. Overall, these results stress the role of the specific high-tech business context at stake when analysing entrepreneurial team composition patterns.